2017
DOI: 10.1111/jopr.12460
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coating of Gypsum‐Based Molds for Maxillofacial Prosthetic Silicone Elastomeric Material: Evaluating Different Microbial Adhesion

Abstract: Surface modification of silicone elastomer yielding a smoother and less porous surface showed lower adhesion of different microorganisms than observed on unmodified surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…In 2012, Jingwei He et al incorporated quaternary ammonium salts into methyl methacrylate (MMA) to form a quaternary ammonium methacrylate that maintained its antibacterial activity without sacrificing its mechanical properties [ 90 ]. Other attempts were made to modify the surface characteristics of the materials, including electronegativity, wettability, and roughness, so as to reduce microorganism adhesion [ 91 , 92 , 93 ]. Nikawa introduced a thermocycling process to a fabricated maxillofacial prosthesis in 2001 and observed Candida albicans growing on it [ 91 ].…”
Section: Development Of Onf Obturatormentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Jingwei He et al incorporated quaternary ammonium salts into methyl methacrylate (MMA) to form a quaternary ammonium methacrylate that maintained its antibacterial activity without sacrificing its mechanical properties [ 90 ]. Other attempts were made to modify the surface characteristics of the materials, including electronegativity, wettability, and roughness, so as to reduce microorganism adhesion [ 91 , 92 , 93 ]. Nikawa introduced a thermocycling process to a fabricated maxillofacial prosthesis in 2001 and observed Candida albicans growing on it [ 91 ].…”
Section: Development Of Onf Obturatormentioning
confidence: 99%
“…The results suggested that the materials exhibited antifungal effects because the surface of these materials was made hydrophobic by this method. In 2007, Khalaf modified silicone elastomer surfaces with different surface roughness and porosity and concluded that a smoother, less porous surface exhibited a lower adhesion of microorganisms [ 93 ]. It was reported that parylene coating reduced the adhesion and aggregation of C .…”
Section: Development Of Onf Obturatormentioning
confidence: 99%
“…3,4 Silikon materyali; kimyasal stabilitesi, yüzey yapısı, dayanıklılığı ve manipülasyon kolaylığı nedeniyle çene yüz protezlerinin üretiminde 50 yılı aĢkın süredir kullanılmaktadır. [5][6][7][8] Ancak bu materyalin renk özelliklerinde zamanla değiĢiklikler ve bozulmalar gerçekleĢmektedir. [9][10][11] Yüz protezlerinin yenilenme gerekliliğindeki temel sebep yüzey yapısı ve renginde gerçekleĢen bu bozulmalardır.…”
Section: Gġrġġunclassified
“…[22][23][24] Bu sebeple yüz protezlerinin yapımı esnasında protezlerin doku ile temasta olan yüzeylerinin pürüzlülüğünün azaltılması hedeflenmektedir. 8 Yüzey pürüzlülüğü ayrıca materyalin mekanik özelliklerinin de önemli bir göstergesidir. Çünkü materyalde gerçekleĢen bozulmalarla birlikte yüzeyde çukurcuklar ve düzensizlikler meydana gelerek yüzey pürüzlülüğü artmaktadır.…”
Section: Gġrġġunclassified